Adaptive noncontact gesture-based system for augmentative communication - REILLY, RICHARD (IEEE, 1999)
An adaptive noncontact gesture-based system for augmentative communication is described. The system detects movement of any anatomical site through the analysis of reflected speckle. This movement is converted into two-dimensional (2-D) cursor coordinates and an adaptive software interface provides click actions and decision strategies. The system requires no accessory to be placed on the user. The system was developed in conjunction with user groups, who participated in the evaluation of the system. The usability results obtained illustrate the utility of the system. The system also compared favorably with other interface solutions.
PUBLISHED
Keywords: adaptive noncontact gesture-based system; adaptive software interface; anatomical site; augmentative communication; click actions; decision strategies; interface solutions; reflected speckle analysis; two-dimensional cursor coordinates